PENGUATAN KAPASITAS SUMBER DAYA MANUSIA BIDANG ADMINISTRASI DALAM MENINGKATKAN PELAYANAN PUBLIK - Lalan Soeherlan S (Universitas Majalengka, 2019)
Strengthening the capacity of human resources administration is an absolute necessity in the effort to improve public services. There are three things that underlie capacity strengthening, namely: the demands of policy on public services; Community demands on public services are growing in accordance with increasing public awareness; And demands of the Revolution 4.0 industry discourse. Aims to prepare human resources administration in order to be able to work professionally in improving public services. The method used is the library research is qualitative interpretative. Results showed that strengthening capacity needs to pay attention to three things, namely the level of development of individual capacity with the target of knowledge, skills, competence and ethics; Conducted through education and training with a five-stage process, namely: 1) involving stakeholders; 2) analyzing capacity and needs; 3) Formulating the response; 4) Apply the response; and 5) evaluation. The education and training process should also pay attention to the capacity aspects, 1) Performance capacity; 2) Personal capacity; 3) Workload capacity; 4) Supervisory capacity; 5) Facility capacity; 6) Support service capacity; 7) Systems capacity; 8) Structural capacity; and 9) Role capacity